Tax Evasion in Indonesia: a Game Theoretical Model - Muhammad Hasyim Ibnu Abbas (Jurnal Ekonomi dan Studi Pembangunan, 2017)
This study aims to analyze the phenomenon of tax evasion in Indonesia by using game theoretical model and referring to Indonesian Tax Laws. This study uses Inspection Game used by Tsebelis and its refinement by Pradiptyo. The game played by 2 representative agents, namely taxpayer who represents all possible parties that can involve to evade and tax investigator who represents all possible parties that concern with taxes, criminal offenses of taxes, and law enforcement. In line with the refined inspection game, the study finds that increasing the severity of penalty may affect the probability of public (taxpayer) to offend (evade) if certain condition fulfilled, according to the Mixed Strategy Nash Equilibrium of the game. Another policy to decrease the probability of taxpayer to evade his tax expense is applying tax incentives policy. The result shows that tax incentives policy is effective rather than increasing the severity of punishment. Because the game is played by players whose scope is wide, it is suggested to develop the game into more specific players and into the next stage of bribery and extortion game which often happen in Indonesia when the taxpayer plays evade and tax investigator plays investigate.Keywords: Tax Evasion, Game Theory, Inspection Game, Refined, Inspection GameJEL Classification: H26, E62